Transição agroecológica no cultivo de rosa x hibrida cv. vegas - Klein, Cláudia Braga Dutra (2022)
The agroecological transition is a gradual process from conventional cultivation to agroecological cultivation. This process was applied to rose producers in the municipality of Passo Fundo, Rio Grande do Sul, with the aim of enabling and promoting the agroecological transition with producers. In chapter I, a search was carried out in the Web of Science Database for publications from the last 14 years (2009–2022) that addressed sustainable floriculture and sustainability in floriculture. 121 publications were found and 26 publications relevant to the research were selected. From this, a bibliometric review was carried out to identify the authors with the greatest production, the place where the studies were developed, the journals in which the articles were published and the year of publication. The results obtained show that there are several studies on how floriculture can present a cleaner production for the environment and for workers. In chapter II, the origins of the municipality of Passo Fundo, the Roselândia neighborhood were addressed through bibliographic research and the Zanotto family, which produces the roses used in this research, through a semi-structured interview. The municipality of Passo Fundo originated from the route of the drovers who cross the country. The Roselândia neighborhood originated from the production of roses by the Pimentel family, and currently this production belongs to the Zanotto family. Chapter III presents the results obtained with the research that was carried out in the field. The experiment is a factorial arrangement, with a randomized block design, 4 replications, 4 treatments (control, homeopathy, efficient microorganisms and with homeopathy plus efficient microorganisms), 13 evaluations and 5 harvests. The production of flowers, buds and plant height were evaluated in the field, totaling 13 evaluations. From the harvests carried out, the length of the floral stem, the length of the bud and the floral diameter were evaluated. The best treatments were observed in plants treated with homeopathy (CH), with efficient microorganisms (EM) and with homeopathy plus efficient microorganisms (CH+EM). There was an increase in the production of buds and in the production of flowers in the evaluations carried out in the field. In the post-harvest analyzes it was observed a greater length of the floral bud and flower stem, and in the floral diameter of the plants submitted to these treatments. Thus, it is proved that the producer has the possibility of entering an agroecological transition process in roses, through the use of homeopathy and efficient microorganisms.